Evaluasi Hasil Pemeliharaan Circuit Breaker Bay Bangil di GI 150 kV KIS Menggunakan Metode TOPSIS - Fernanda, Muhammad Rofi; Budisusila, Eka Nuryanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Substation using the TOPSIS method. The research addresses the need for objective and data-driven maintenance assessment to ensure reliable power supply. The study employs an applied quantitative case study approach, focusing on ABB-type circuit breakers maintained in 2022 and 2024. The population consists of all circuit breakers at the substation, with samples taken from phases R, S, and T. Data were collected using instruments such as Kyoritsu KEW 3125A, Megger Mjolner 200, Vanguard CT-6500, and Kyoritsu 4105A, and analyzed using Microsoft Excel and the TOPSIS decision support system. Results show a decline in technical performance in 2024 compared to 2022, especially in phases S and T, which require further attention. The conclusion highlights the effectiveness of the TOPSIS method in providing a comprehensive evaluation and recommends routine, integrated application for future maintenance prioritization.